2016
DOI: 10.1159/000445761
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Methamphetamine Exposure Inhibits Methamphetamine Cue Conditioning and Reduces Dopamine Concentrations in Adult N2 <b><i>Caenorhabditis elegans</i></b>

Abstract: Methamphetamine (MAP) addiction is substantially prevalent in today's society, resulting in thousands of deaths and costing billions of dollars annually. Despite the potential deleterious consequences, few studies have examined the long-term effects of embryonic MAP exposure. Using the invertebrate nematode Caenorhabditis elegans allows for a controlled analysis of behavioral and neurochemical changes due to early developmental drug exposure. The objective of the current study was to determine the long-term be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…C. elegans have conserved neurobiological systems with established mapping of all neurons and synapses in the entire animal. We have shown that, C. elegans develops a conditioned preference for cues that had previously been paired with either cocaine or methamphetamine exposure that is similar to findings using place conditioning with rats and mice ( Musselman et al, 2012 ; Katner et al, 2016 ). Moreover, conditioning required functional dopamine neurotransmission ( Musselman et al, 2012 ).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…C. elegans have conserved neurobiological systems with established mapping of all neurons and synapses in the entire animal. We have shown that, C. elegans develops a conditioned preference for cues that had previously been paired with either cocaine or methamphetamine exposure that is similar to findings using place conditioning with rats and mice ( Musselman et al, 2012 ; Katner et al, 2016 ). Moreover, conditioning required functional dopamine neurotransmission ( Musselman et al, 2012 ).…”
Section: Introductionsupporting
confidence: 69%
“…Cholesterol was not included in the salt-free agar in order to obtain clearer images of worms during testing. Although the lack of salts and cholesterol in the agar may have long-term effects on worms, our previous work indicating intact cue-conditioned learning ( Musselman et al, 2012 ; Katner et al, 2016 ) and the differential responses with the SOAs vs. controls (food or benzaldehyde) show that the agar preparation as used in this paradigm does not prevent normal chemotaxic responses.…”
Section: Methodsmentioning
confidence: 75%
“…3b,c), they could be useful as an animal model for the in vivo screening of potential antagonists for opioid expression. In fact, C. elegans has already been demonstrated to study chemical antagonists against cocaine and methamphetamine exposure, and these experiments yielded similar findings to those obtained using place conditioning with rats and mice 55,56 . Furthermore, C. elegans and vertebrates share a conserved opioid system 4 , the effects of pheromone on the expression of nlp-24, which encodes a β-endorphin-homolog, suggest possible approaches for modulating opioid drug function via pheromone mimetics and preference via manipulation of genetic or biochemical conditions.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, a relatively short life cycle and a 3-day generation time from egg to adult can lead to a dramatic increase in the pace of discovery at a fraction of the cost inherent when using higher level organisms. We have discovered that, like mammals and other invertebrates, C. elegans also develops a conditioned preference for cues after previous pairings with methamphetamine or cocaine that is dependent on dopamine neurotransmission [9,10]. Together, these data indicate that invertebrates, specifically C. elegans, show behavioral responses to addictive drugs that are consistent with those of higher level organisms.…”
Section: Accepted Manuscriptmentioning
confidence: 76%